Effect of aloe vera gel on the quality of papaya (Carica papaya) during postharvest storage - Fadzilah Songkongon (2018)
vi
ABSTRACT
Papaya fruit postharvest losses are considered quite high due to improper handling which triggers the invasion of fungus. Employing edible coating with desirable physical, sensory and microbiological properties to papaya can reduce detrimental changes and consequently extend their shelf-life. Aloe verais one of an excellent candidate for fruit coating. The aim of this research was to evaluate the influence of Aloe vera at different concentrations (0, 15, 25 and 50%, v/v) on some papaya quality characteristics during 15 days of storage at room temperature. During storage, observations on moisture content, weight loss, firmness, ascorbic acid, total phenolic content (TPC) and DPPH assay scavenging were recorded at three days of interval. Uncoated papaya has significantly different with coated papaya for all of the parameters studied. However, different treatment shows different effect to the fruit quality. Coated papaya at 25% and 50% of Aloe vera gel did not show significant differences in moisture content, ascorbic acid, and DPPH scavenging activity. For firmness and weight loss, 50% of Aloe vera has the highest percentage of firmness and lowest percentage of weight loss. However, the application of 25% of Aloe vera showed the higher content of total phenolic content than 50% but has no significant different with 15% Aloe vera. Overall, the results showed that 25% Aloe vera gel is the best coating concentration because of the physico-chemical content in the papaya. In conclusion, Aloe vera gel coating is a good agent to extent the shelf-life of papaya hence reducing postharvest losses.
Project paper (B.Hort.Sc.) - Universiti Putra Malaysia, 2018.